Girls in pants the third summer of the Sisterhood - Brashares, Ann (Delacorte Press, 2006)
The members of the Sisterhood of the Traveling Pants graduate from high school and spend their last summer before college learning about life and themselves. Includes readers' guide with discussion questions and an interview with the author.